The Influence Of Digital Literacy And Academic Support On Entrepreneurship Intention Through Internal Locus Of Control (Study Of S1 Students Class Of 2019 Faculty Of Economics And Business, State University Of Malang) - Agung Nugroho; Sri Umi Mintarti Widjaja; Sugeng Hadi Utomo (Cita konsultindo, 2023)
The current orientation of society is also always on the formal employment sector so that when the formal employment sector is sluggish, people do not try to create their jobs in the non-formal or private sectors. This is why the level of public unemployment is still quite high in Indonesia. The highest unemployment rate in Indonesia is created by the educated group. This type of research uses a quantitative approach with a proportional random sampling method. The research hypothesis uses a Structural Equation Model (SEM) based on (PLS). The variables in this study are (1) Digital Literacy, (2) Academic Support, (3) Entrepreneurial Intentions, and (4) Internal locus of control. The population of this study was students of the Faculty of Economics and Business, the State University of Malang, class of 2019, totaling 982 students. The sampling technique used the Cochran formula so that a sample of 243 students was obtained. The results of this study are (1) There is a positive and significant influence of digital literacy on the entrepreneurial intentions of FEB UM 2019 students so the first hypothesis is accepted. (2) There is an influence of academic support on the entrepreneurial intentions of 2019 FEB UM students, so the second hypothesis is accepted. (3) There is an effect of digital literacy on the internal locus of control of 2019 FEB UM students, so the third hypothesis is accepted. (4) There is an influence of academic support on the internal locus of control of FEB UM 2019 students so the fourth hypothesis is accepted. (5) There is an internal locus of control influence on the entrepreneurial intentions of 2019 FEB UM students so the fifth hypothesis is accepted. (6) There is an effect of digital literacy on entrepreneurial intentions through the internal locus of control in 2019 UM FEB students so the sixth hypothesis is accepted. (7) There is an influence of academic support on entrepreneurial intentions through the internal locus of control in 2019 UM FEB students so that the seventh hypothesis is accepted